2012
DOI: 10.12659/ajcr.882234
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of pulmonary metastases of Bellini duct carcinoma with cisplatin, gemcitabine and bevacizumab: a case report

Abstract: SummaryBackground:Bellini carcinomas, rare tumors of kidney, are aggressive and have a poor prognosis. For these cancers, there is no standard treatment regimen and chemotherapy for urothelial cancer is usually used.Case Report:In a 44-year-old man with hematuria, a tumor was diagnosed in the right kidney. After radical nephrectomy, pathologic analysis revealed Bellini carcinoma, staged pT3apN0, Fuhrman grade 3. Secondary pulmonary lesions occur one year later. Chemotherapy (gemcitabine, cisplatin and bevacizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…7 Procopio and colleagues assessed 13 patients with CDC receiving targeted therapies and 3 patients experienced periods of disease stabilization. 19 Miyake and CUAJ • September-October 2015 • Volume 9, Issues 9-10 E592 ciszewski et al collecting (Bellini) duct carcinoma colleagues 20 and Chua and colleagues 21 presented case reports of partial response of metastatic CDC after sunitinib therapy. Ansari and colleagues reported a response, with minimal side effects, to sorafenib in a patient with metastatic CDC.…”
Section: Discussionmentioning
confidence: 99%
“…7 Procopio and colleagues assessed 13 patients with CDC receiving targeted therapies and 3 patients experienced periods of disease stabilization. 19 Miyake and CUAJ • September-October 2015 • Volume 9, Issues 9-10 E592 ciszewski et al collecting (Bellini) duct carcinoma colleagues 20 and Chua and colleagues 21 presented case reports of partial response of metastatic CDC after sunitinib therapy. Ansari and colleagues reported a response, with minimal side effects, to sorafenib in a patient with metastatic CDC.…”
Section: Discussionmentioning
confidence: 99%
“…Staehler et al (11) reported two stage T3aN2M0 CDC cases treated with RN plus combined therapy (first line, gemcitabine + cisplatin; second line, sunitinib); both patients succumbed to the disease 8 months after the initial diagnosis. However, Barrascout et al (12) described a patient with T3aN0m0 CDC treated with RN plus combined therapy (gemcitabine, cisplatin and bevacizumab) who survived >35 months following the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (one phase II single arm trial with 5 patients and one case report) suggested that addition of bevacizumab to platinum-based chemotherapy could improve efficacy of chemotherapy. These preliminary results need to be confirmed (8,9). Bevacizumab is still under evaluation in combination with GC based-chemotherapy in metastatic renal CDC [BEVABEL GETUG-AFU phase 2 Trial (NCT02363751)].…”
Section: Introductionmentioning
confidence: 99%